THE DEVELOPMENT OF PHILOSOPHICAL RATIONALIST THOUGHTS IN ANCIENT ATHENS - Akhmatov Shakhzod Boymirza ugli (Web of Journals Publishing, 2025)
In this article, we can see the philosophical rationalist ideas that began to emerge in ancient Athens. We will get acquainted with the views of scientists who were engaged in philosophy in the early period, the processes of trying to rationally understand the world. In addition, we will learn about the efforts to rationally understand man.
Keywords: Rational thoughts, Anaxagoras, Plato, Socrates, thing, feeling, atom, love, quarrel.